Manajemen Pengelolaan dan Pengembangan Usaha pada UMKM di Kabupaten Bogor (Studi Kasus pada Usaha Makanan Fast Food) - Dedi Muliadi (Departement of Mathematics Education, 2023)
The purpose of this research is to describe the management and business development of MSMEs in Bogor Regency, to analyze the internal and external environment, and to plan business development in the fast food business. Data collection method used in this research is interview. The data analysis method used is descriptive qualitative analysis. Based on the results of data analysis, the authors found that the management and development of business, especially fast food in the internal environment around the place of business has been going well in terms of human resources, financial aspects, and production and operational aspects. Meanwhile, the analysis of the external environment shows that the fast food business has a weak competitive position because it does not have product differentiation. The strategy used by the company is a market development strategy which is obtained from the results of the SWOT analysis and the grand strategy matrix.